Media Pembelajaran Pendidikan Inklusi Sahabat Kecil Therapy & Learning Center di Medang - Ika, Ika; Handayani, Alfy Dian; Febrianti, Lilis; Maemunah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out the learning media used by inclusive educators at the little friend therapy & learning center in Medan. This type of research is descriptive qualitative. The main informants consisted of inclusion tutors and school principals. Data collection techniques in this study used interviews, observation, and documentation. Data analysis from the results of this study was carried out by descriptive analysis. The results showed that 1) learning media in inclusive education at Kawan Kecil Therapy & Learning Centers in Medan used several therapeutic tools or learning tools, namely alphabet boards, puzzles, and sandboxes in training children's creativity, very important to facilitate learning. 2) the implementation of learning at the little friend therapy & learning center in Medan where the implementation was carried out there were two sessions to facilitate the learning process. 3) Obstacles encountered during the learning of inclusive children at the little friend therapy & learning center in Medan, one of which is the existence of hyperactive children, uncontrolled emotions in learning and even a disconnection between the teacher and parents of students, solutions that need to be made to maximize inclusion programs in schools, including activating school evaluation programs, participating in training or BIMTEK related to inclusion services, and supervisory relationships or networks to monitor teacher work programs so that they are better and planned. Keywords: Learning Media, Inclusive Education